Judicial Waiver Policy and Practice: Persistence, Seriousness and Race - Feld, Barry C (1995)
One of the most controversial contemporary criminal policy issues is whether serious or chronic young offenders should be tried and sentenced as juveniles or adults. Defining the boundary between juvenile and criminal courts depends upon the answers to a host of inter-related questions: Who are serious juvenile offenders? On the basis of what characteristics are they identified? Who should decide which system will deal with them and why? Does it make any difference, either symbolically or in terms of public safety, whether states try and sentence some youths as juveniles or adults? The diversity of legislative strategies to resolve these dilemmas reflect the practical and theoretical complexity of the problem.